[BP.08.01] EVALUATION OF RETINAL MICROPERFUSION AND ARTERIOLAR STRUCTURE IN PATIENTS WITH FIBROMUSCULAR DYSPLASIA – THE POLISH REGISTRY FOR FIBROMUSCULAR DYSPLASIA (ARCADIA-POL STUDY). (September 2017) - Warchol-Celinska, E.; Gosk-Przybylek, M.; Harazny, J.; Binczyk, E.; Szymanek, K.; Hanus, K.; Januszewicz, M.; Prejbisz, A.; Swiatlowski, L.; Ostrowski, T.; Galazka, Z.; Blazejewska-Hyzorek, B.; et al.
Abstract : Objective: To compare retinal microperfusion and arteriolal structure between patients with fibromuscular dysplasia (FMD) enrolled to the ARCADIA-POL study and patients with essential hypertension (EHT). Design and method: From the 144 patients with confirmed FMD in any vascular bed enrolled in the ARCADIA-POL study since January 2015, we analyzed data regarding retinal microperfusion and arteriolar structure available from 119 patients (95F, 24 M, mean age: 45.6 ± 14.8 years). All patients underwent detailed clinical evaluation including ABPM, biochemical evaluation and biobanking as well as duplex Doppler of cervical and abdominal arteries and whole body angio-CT. We also evaluated 66 age, gender, body mass index, glycemic status, blood pressure (BP) levels and number of medication (p > 0.05) matched patients (37F, 29 M, mean age: 48.7 ± 10.5 years) with EHT. Retinal microperfusion (RCF) and retinal arterioles were assessed using scanning laser Doppler flowmetry (SLDF). The parameters of retinal morphology: outer diameter (AD), lumen diameter (LD), wall/lumen ratio (WLR), wall thickness (WT), and wall cross-sectional area (WCSA) were determined by automatic full-field perfusion imaging analysis (AFFPIA V.4.011). Results: When comparing 119 patients with FMD to the matched group of patients with EHT we observed no significant differences in in parameters describing retinal morphology. In further analysis we included 41 patients with confirmed FMD in cervical and/or intracranial arteries and/or intracranial aneurysms (31F, 10 M, mean age 45.9 ± 14.3ys) and we compared them to 56 matched patients (p > 0.05) with EHT (32F, 24 M, mean age: 49.8 ± 11.3ys). Patients with FMD affecting cervical and/or intracranial arteries were characterized by lower WLR (0.34 ± 0.08 vs. 0.39 ± 0.09, p = 0.06) and lower WT (13.1 ± 3.4 vs.14.8 ± 3.7 μm, p = 0.02) and lower WCSA (3716.5 ± 1290.5 vs. 4277.4 ± 1387.9 μm 2, p = 0.05) as compared to patients with EHT. There was no differences in AD, LD, nor RCF between the groups. Conclusions: In our ongoing ARCADIA-POL study we observed significant changes in retinal arterioles structure in patients with FMD affecting carotid and/or intracranial arteries. This may partially reflect altered responsive properties of small arteries to BP changes in patients with FMD as compared to patients with EHT.